A Deconstructive Reading of the Trauma in Martin Aleidaâ€™s â€œTanpa Pelayat dan Mawar Dukaâ€ - Kristono, Lany (Journal of Language and Literature, 2015)
Being one of the most widely discussed turmoil, the 1965 tragedy must have left a cultural trauma to those involved, particularly the victims. As one victim of the event, Martin Aleida should know better how such a trauma represents itself. Therefore, this study would like to examine the trauma in his work â€œTanpa Pelayat dan Mawar Dukaâ€ (â€œWithout Mourners nor Rosesâ€): who suffers from the trauma, how they respond to the trauma, and the ideology underlying the trauma from the perspective of Deconstruction. Derridaâ€™s Deconstruction has been selected as the story contains paradoxes and this study adopts Jeffrey Alexanderâ€™s belief that trauma is socially constructed instead of a result of the event itself. A scrutiny of the trauma in the story confirms Alexanderâ€™s notion of the trauma and the dominant ideas of the ruling class, including gender power relations, which shape the charactersâ€™ attitudes towards their trauma and their interactions. The findings also reflect the solidity of gender power relations.